DEVELOPMENT OF CIPROFLOXACIN RESISTANCE DUE TO CHROMOSOMAL MUTATIONS INDUCED BY 2-NITROFLUORENE - Birosova, Lucia; Mikulasova, Maria (Biomedical papers, 2005)
In this paper we investigated the ability of 2-nitrofluorene to induce mutations leading to antibiotic resistance in quinolone-sensitive strain Salmonella typhimurium. After preincubation of bacteria with 2-nitrofluorene, the frequency of mutation to ciprofloxacin resistance was 57 fold higher than in the case of spontaneous mutability. Some of resultant resistant colonies showed a great increase of ciprofloxacin MIC.
Keywords: 2-Nitrofluorene/Antibiotic resistance/Ciprofloxacin/Salmonella typhimurium